USAGE OF THE METACOGNITIVE METHODS IN DEVELOPING WRITING ONLINE FOR HIGH SCHOOL LEARNERS - Qurbonova Durdona Xayotjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This research gives brief information about benefits of the usage of the metacognitive method in online teaching writing skills of high school learners.